2021
DOI: 10.1177/07482337211013321
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the AS3MT gene are associated with arsenic methylation capacity and damage to the P21 gene in arsenic trioxide plant workers

Abstract: Epidemiological evidence suggests that the metabolic profiles of each individual exposed to arsenic (As) are related to the risk of cancer, coronary heart disease, and diabetes. The arsenite methyltransferase ( AS3MT) gene plays a key role in As metabolism. Several single nucleotide polymorphisms in the AS3MT gene may affect both enzyme activity and gene transcription. AS3MT polymorphisms are associated with the proportions of monomethylarsenic acid (MMA) and dimethylarsenic acid (DMA) in urine as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, in various nontumorigenic cell lines, treatment with N-acetyl-D-glucosamine for 3 days resulted in genome instability [ 35 ]. In a study by Ni et al [ 36 ] on a group of workers exposed to iAs, DNA damage to the P21 gene fragments was observed, which was associated with the reduced methylation of iAs (positively associated with the percentage of MMA and negatively with the percentage of DMA in the urine). The results of the aforementioned study indicated that iAs exposure is associated with an increase in N-acetyl-D-glucosamine signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in various nontumorigenic cell lines, treatment with N-acetyl-D-glucosamine for 3 days resulted in genome instability [ 35 ]. In a study by Ni et al [ 36 ] on a group of workers exposed to iAs, DNA damage to the P21 gene fragments was observed, which was associated with the reduced methylation of iAs (positively associated with the percentage of MMA and negatively with the percentage of DMA in the urine). The results of the aforementioned study indicated that iAs exposure is associated with an increase in N-acetyl-D-glucosamine signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic As metabolism can be influenced by genetic differences, which may predispose individuals to adverse health outcomes related to iAs exposure [ 12 ]. Previous studies have shown that polymorphisms in the AS3MT gene may be associated with reduced gene expression and enzymatic activity, which were correlated with urinary MMA and DMA levels [ 13 ]. Other studies reported that single-nucleotide polymorphisms (SNPs) in the AS3MT gene were related to iAs exposure in drinking water and were associated with lower percentages of MMA and higher percentages of DMA in urine [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%